Strategies for Sustainable Mine Reclamation: Case Study of the Meghahatuburu Iron Ore Mine - Murmu M.; Behera S. (My University, 2025)
The demand for raw materials is increasing rapidly, leading to higher production targets for mining industries. Currently, large-scale opencast mining operations are causing extensive damage to forest areas, agricultural land, and various habitats for humans and animals. Despite these negative impacts, mining plays a crucial role in our national economy, serving as the second backbone of the country after agriculture. Given the inevitability of mining operations, it is essential to carry them out in a sustainable manner, minimizing or even eliminating environmental harm. This study focuses on the challenges associated with iron ore mining and emphasizes the significance of ecological restoration and land reclamation in mitigating environmental consequences. The focus of this research work is the implementation of a comprehensive procedural approach to achieve sustainable mine reclamation in an easy way. The primary objective is to restore the biodiversity of the Saranda Forest ecosystem. To accomplish this, a three-tier plantation model was adopted, involving the strategic planting of 2,664 trees and 3,136 herbs/shrubs in 1.5 hector degraded backfilled area. This initiative aims to rehabilitate the degraded land that has been adversely affected by mining activities. © 2024 Geological Society of India, Bengaluru, India.